Clinical phenotype and allergen sensitization in the first 2 years as predictors of atopic disorders at age 5 years. Issue 1 (December 2015) - Quah, Phaik; Loo, Evelyn; Lee, Gabriella; Kuo, I-Chun; Gerez, Irvin; Llanora, Genevieve; Chan, Yiong; Aw, Marion; Shek, Lynette; Lee, Bee
Abstract Introduction From a birth cohort of at-risk Asian infants, we prospectively investigated the role of early onset allergen sensitization and clinical phenotypes as risk factors for atopic disorders at the age of 5 years. Methods and materials The study recruited 253 families with a history of allergic disease in a first degree relative from an antenatal clinic in Singapore. The children were followed prospectively to assess clinical outcomes and skin prick test was performed at 2 and 5 years of age. Results Allergen sensitization (food and/or house dust mites) alone at 2 years of age was not associated with increased risk of wheeze and eczema at 5 years. However, the clinical phenotype (eczema and wheeze) with or without the presence of concomitant allergen sensitization at 2 years increased this risk. For eczema, eczema alone at year 2 increased the risk of eczema at year 5 (adjOR = 7.1; 95 % CI: 1.8–27.8) and this was further increased by the presence of allergen sensitization (adjOR = 25.4; 95 % CI: 4.7–138.5) and the concomitant presence of both wheeze and allergen sensitization (adjOR = 64.9; 95 % CI: 4.7–900.0). For wheeze, wheeze alone at 2 years (adjOR = 4.5; 95 % CI: 1.4 -14.8), and wheeze with concomitant allergen sensitization and eczema (adjOR = 13.9; 95 % CI: 1.2–168.5) increased the risk of wheeze at 5 years. The exception was rhinitis, where allergen sensitization alone at 2 years (adjOR = 5.6; 95 % CI: 1.1–29.2) increased the risk of rhinitis at 5 years. Early onset of eczema at 2 years also increased the risk of rhinitis (adjOR = 6.8; 95 % CI: 2.0–23.1). Conclusion In this Asian birth cohort, the clinical phenotype (eczema and wheeze) with or without concomitant allergen sensitization in the first 2 years of life were strong predictors of atopic disorders at 5 years.